h - Dunkelman, Orr.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Cryptographers' Track at the RSA Conference 2012, CT-RSA 2012, held in San Francisco, CA, USA, in February/March 2012. The 26 revised full papers presented were carefully reviewed and selected from 113 submissions. The papers are organized in topical sections on side channel attacks, digital signatures, public-key encryption, cryptographic protocols, secure implementation methods, symmetric key primitives, and secure multiparty computation.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Computer Science; Data Encryption; Discrete Mathematics in Computer Science; Systems and Data Security; Computer Communication Networks; Algorithm Analysis and Problem Complexity